PENGARUH KARAKTERISTIK PERUSAHAAN TERHADAP CORPORATE SOCIAL RESPONSIBILITY, DAN DAMPAKNYA TERHADAP NILAI PERUSAHAAN - Yuliana, Feni Indah (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2013)
There are two models of testing in this research; the purpose of the first testing model is to find out the influenceof company characteristic to the CSR disclosure while the purpose of the second testing model is to find out theinfluence of CSR to the company value. The result of the first model shows that ROA, company size, companyprofile, and company category are significantly influence to the CSR disclosure. The granting of ISRA does notsignificantly influence to the CSR disclosure. The result of the second model shows that the CSR disclosure issignificantly influence to the company value.Keywords: ROA, Company Size, ISRA, Company Profile, Company Category, CSR, and Company Value.